Sc(OTf) 3 catalysed multicomponent synthesis of chromeno[2,3-d]pyrimidinetriones under solvent-free condition - Kumari S.; Kumar D.; Gajaganti S.; Srivastava V.; Singh S. (My University, 2025)
An efficient, simple, and environmentally friendly synthesis of a series of chromeno[2,3-d]pyrimidine-trione derivatives has been accomplished via the three-component reaction of a barbituric acid, dimedone/cyclohexane-1,3-dione, and aromatic aldehydes using Sc(OTf) 3 as a recyclable catalyst under solvent-free condition. This method exploits the use of Sc(OTf) 3 as a Lewis acid catalyst in organic synthesis and offers many rewards such as excellent product yield and easy work-up procedure. Harmless reaction conditions, as well as the absence of side-products, are another green aspects of this protocol. © 2019, © 2019 Taylor & Francis Group, LLC.